Long-term assessment of electrocardiographic and echocardiographic findings in Norwegian elite endurance athletes - Bjørnstad, H. H.; Bjørnstad, T. H.; Urheim, S.; Hoff, P. I.; Smith, G.; Maron, B. J. (Cardiology, 2009)
Objectives: The long-term outcome and clinical significance of athlete's heart has been debated and more longitudinal data are needed. We present a prospective 15 years' follow-up study of ECG and echo findings in elite endurance athletes following the end of their competitive career. Methods: Clinical evaluation, ECG, ambulatory Holter recording and echocardiography were performed in 30 top-level endurance athletes with a mean age of 24 years with follow-up 15 years later. All had then ended their competitive career, but still performed recreational sports activities. Results: No clinical events were reported. Average resting heart rate was unchanged (53.5 ± 10 at baseline and 55.4 ± 11 at follow-up, p = n.s.), complex ventricular arrhythmias did not occur and the number of ventricular premature beats (VPBs) were 0.4 ± 0.8/h at baseline and 3.8 ± 10/h at follow-up (p = n.s.). In a subgroup of 4 subjects with >100 VPBs per hour at follow-up left ventricular mass was increased compared to the others (p < 0.03). Furthermore, regression of sino-atrial (SA) and atrioventricular (AV) blocks was shown. There were no cases of atrial flutter or fibrillation. There was a slight reduction in mean left ventricular wall thickness (9.9 ± 1.2 vs. 9.5 ± 1.4 mm, p < 0.05) and a highly significant reduction of relative wall thickness (0.38 vs. 0.35, p < 0.001). Left ventricular end-diastolic volume (68 ± 6 vs. 70 ± 7 ml ml/m2, p = n.s.) and left ventricular mass (109 ± 19 vs. 107± 19 g/m2, p = n.s.) were unchanged when corrected for body surface area and ejection fraction (EF) increased (60 ± 7 vs. 67 ± 6%, p < 0.01). Parameters of left ventricular diastolic function were normal both at baseline and follow-up. Conclusions: There was no evidence of deleterious cardiac effects of previous top-level endurance athletic activity at 15 years' follow-up.